Confinement-induced unatomic trimer states - Rosa, D. S.; Francisco, R. M.; Frederico, T.; Krein, G. [UNESP]; Yamashita, M. T. [UNESP] (American Physical Society (APS), 2024)
The signature of an unatomic system is revealed by a continuous scale invariance that appears during a progressive dimensional squeezing of a resonantly interacting trimer. The unatomic regime is reached at the dimension D¯, which for three identical atoms is found to be D¯=2.292-below this value, the trimer wave function at short distances displays a power-law behavior. The fingerprint of this crossover is a sharp evolution of the contacts that characterizes the trimer momentum distribution tail.
Keywords: Continuous scale; Momentum distributions; Power law behaviour; Scale invariance